First Report of Rose Bent Neck Caused by Sclerotinia sclerotiorum on Commercial Cut Roses (Rosa hybrida L.) - Melissa Muñoz; Logan E. Behnke; James E. Faust; Guido Schnabel (Horticulturae, 2023)
Cut roses are highly valuable ornamentals and their profitability depends on the flower postharvest performance. Bent neck symptoms in roses make them unmarketable and are typically related to physiological disorders, bacteria accumulation in the vase solution, and Botrytis cinerea infection. Unusual bent neck symptoms were observed in 4.7% of ‘Orange Crush’ roses from two commercial shipments, resulting in complete flower collapse. This research was aimed to determine the causal agent of the bent neck symptoms. Following incubation in a humid chamber, symptomatic roses evolved in water-soaked lesions with the presence of white mycelium and sclerotia development. Fungal isolations and molecular characterization were performed and Sclerotinia sclerotiorum was identified as the causal agent of rose bent neck. Therefore, when bent neck symptoms are observed, S. sclerotiorum incidence should be considered to avoid possible outbreaks.